Shiism and the essence of Shiite culture from the point of view of Allameh Tabatabai - Mohammadreza Ebrahimnejad (پژوهش‌نامه کلام تطبیقی شیعه, 2023)
One of the things that Allameh Tabatabai cared about was protecting the Shia religion and culture. Allameh had come to the conclusion that the West's understanding of the Shiite religion is incomplete and negative, and with the aim of compensating and correcting this great deficiency, he started a wide-ranging scientific struggle. Among the important features of Shia that Allameh left no stone unturned in proving and popularizing, was the Qur'an-orbital method or "interpretation of the Qur'an by the Qur'an." In this article, an attempt has been made to analyze and present the process of his scientific efforts in this field. Allameh has traveled this scientific path in two negative and positive stages; In the first stage, the major and common methods of interpretation - that is, the hadith, theological, philosophical, Sufi, sensualist and theological methods - Ramarafi has expressed the common and specific criticisms of each with arguments, including that all these methods are actually adaptations, not interpretations; In the second stage, by using the verses of the Qur'an, the traditions and the traditions of the Ahl al-Bayt (PBUH), he mentioned the acceptability of interpreting the Qur'an through the Qur'an and its necessity along with its valuable results, and finally reached the goal that the method of interpreting the Qur'an to the Qur'an is the only method of the Ahl al-Bayt. peace be upon him and it should be considered one of the characteristics of the Shia religion.